(untitled) (Revista Argentina de Musicología, 2026)
Graphic art was a key tool in the strategies of resistance groups both within and outside Uruguay during the civil-military dictatorship that the country endured between 1973 and 1985, and in the years immediately preceding it. In this paper, I examine the almanacs published by the Club de Grabado de Montevideo, an institution that played a significant role in cultural resistance, and posters from various sources. The latter corpus includes handcrafted pieces, particularly from the late 1960s and the early years of the dictatorial regime, as well as works by prominent professionals such as Blankito and Carlos Palleiro. I focus particularly on the posters preserved in the Alfredo Zitarrosa Archive. I identify the main iconographic themes in these materials, amongst which the guitar stands out as a musical motif and barbed wire as a general motif. I develop an analysis based on visual rhetoric: the presence of metaphors, synecdoches, allegories and their relationship with the ideology that accompanied these activities of resistance, denunciation and solidarity. Editorial History: Received: April 17, 2026 Accepted: June 29, 2026